PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA BAPPEDA KABUPATEN SITUBONDO - Dewi, Elsa Aulia; Tulhusnah, Lusiana; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The Situbondo Regency Regional Development Planning Agency (BAPPEDA) is a government agency. BAPPEDA has the task of assisting the Regent in carrying out the supporting functions of Government Affairs in the Planning and Research and Development Sector. The purpose of this study was to analyze and examine the effect of leadership style and work discipline on the performance of state civil servants through job satisfaction as an intervening variable. The sampling technique was determined by saturated sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that the leadership style significant effect on job satisfaction, work discipline has a significant effect on job satisfaction, leadership style has a significant effect on performance, work discipline has a significant effect on performance, job satisfaction has a significant effect on performance. The results of the indirect effect hypothesis test show that the variable leadership style on performance through job satisfaction has a significant positive effect, work discipline on performance through job satisfaction has a significant positive effect.